2017
DOI: 10.1002/jbmr.3296
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemic Disorders in Children

Abstract: Hypercalcemia is defined as a serum calcium concentration that is greater than two standard deviations above the normal mean, which in children may vary with age and sex, reflecting changes in the normal physiology at each developmental stage. Hypercalcemic disorders in children may present with hypotonia, poor feeding, vomiting, constipation, abdominal pain, lethargy, polyuria, dehydration, failure to thrive, and seizures. In severe cases renal failure, pancreatitis and reduced consciousness may also occur an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 145 publications
(365 reference statements)
2
94
1
8
Order By: Relevance
“…However, genetic testing should be carried out in PHPT patients who meet the following criteria: young age (<45 years of age); multigland disease; carcinoma or atypical adenoma; a firstdegree relative who is a known mutation carrier; an index case with 2 or more MEN syndrome-associated tumors. 2) In cases where MEN affects multiple glands, subtotal or total parathyroidectomy is recommended. 19) If ectopic parathyroid adenoma is well localized and ioPTH level decreases sharply after resection, minimally invasive parathyroidectomy without bilateral neck exploration could be a better option to avoid unnecessary morbidity in children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, genetic testing should be carried out in PHPT patients who meet the following criteria: young age (<45 years of age); multigland disease; carcinoma or atypical adenoma; a firstdegree relative who is a known mutation carrier; an index case with 2 or more MEN syndrome-associated tumors. 2) In cases where MEN affects multiple glands, subtotal or total parathyroidectomy is recommended. 19) If ectopic parathyroid adenoma is well localized and ioPTH level decreases sharply after resection, minimally invasive parathyroidectomy without bilateral neck exploration could be a better option to avoid unnecessary morbidity in children.…”
Section: Discussionmentioning
confidence: 99%
“…1) The causes of hypercalcemia in children can be classified as parathyroid hormone (PTH)-dependent or PTH-independent and may be either congenital or acquired. 2) Primary hyperparathyroidism (PHPT) accounts for > 90% of hypercalcemia in adults, and most patients with PHPT present with a single adenoma (80%) or hyperplasia (15%-20%) of the parathyroid gland. Parathyroid carcinoma occurs rarely, accounting for <1% of all cases of PHPT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Pediatric patients with hypercalcemia were far fewer cases than the incidence rate in adult patients and one of the causes of hypercalcemia was impaired of parathyroid hormone production and kidney disorders. 16 And this applied also in this study because we only found three hypercalcemia patients.…”
Section: Demographic Profile Of Patientsmentioning
confidence: 97%